"Look do dia": consumo conspícuo de fast fashion e construções identitárias no instagram - Dantas, Bruna Lourena de Lima (2018)
Conspicuous consumption, in which motivations are aimed at achieving status through the display of goods, is enhanced in the online environment, where identity constructions are derived from interpersonal relationships and the meanings that goods carry. Instagram presents itself as an online social network in which the consumption of fast fashion is notorious and can contribute to the constructions of identity of fashion consumers. From this perspective, the current academic paper has as general objective to analyze the influence of the conspicuous consumption of fast fashion products in Instagram in the process of identity construction of women. In order to accomplish it, the methodology of the study has a qualitative approach using data triangulation with the techniques of participant observation, interview and online focus group. The interviews were conducted with eleven women, who are Instagram users and potentially fast fashion consumers, while the online focus group was elaborated in three sessions with seventeen women, divided into three groups, respectively, and the observation was performed in seven months. Using the interpretative paradigm, data analysis was performed using the technique of content analysis. The categories of analysis emerged from the theory put forward in a research script, which directed the collection of data, that is, the use of Instagram, consumption in the construction of identity, conspicuous consumption and consumption of fast fashion. From the first category, it is concluded that the social network in question is a significant part of the daily life of the participants, being determinant for consumption. The interactions present in Instagram allow social relations to be constructed and demonstrated. For this, the consumption of fashion in the construction of identity provokes the need for acceptance and belonging, establishing senses through consumer goods, while conspicuous consumption is found in Instagram through the need to impress people with the clothes consumed; and, on the results of personal satisfaction, approval of people, and association in social groups. The results show conspicuous consumption of fast fashion products in Instagram inserted in a dynamic of demonstration, acceptance and affiliation in social groups that creates meaning and builds contextual identities able to accompany women and suffer variations as they use the goods for their representations.